Transformation of rural landscapes in the Vietnamese Mekong Delta from 1990 to 2019: a spatio-temporal analysis. Issue 26 (13th December 2022) - Nguyen, Ho; Trung, Ta Hoang; Phan, Duong Cao; Anh Tran, Thong; Thi Hai Ly, Nguyen; Nasahara, Kenlo Nishida; Prishchepov, Alexander V.; Hölzel, Norbert
Abstract: In this study, we aimed to explore the rural landscape transformation through the analysis of land use/land cover (LULC) spatio-temporal dynamics in the entire Vietnamese Mekong Delta over the three decades, using Landsat imageries and a supervised random forest classifier. Results indicated that in the 1990s, dominant LULC types were arable cropland, wetland, and permanent crops, which covered approximately half of the delta, 28% and 8%, respectively. From 1990 to 2019, the wetland area decreased from 28% to 5% due to the expansion of aquaculture and the arable cropland. The aquaculture, however, expanded more rapidly than other land use conversions, namely, from 2% to 19%. Although mangrove forests slightly recovered by 58 km 2 from 2005 to 2019, the overall trend (1990-2019) showed an intense loss of 740 km 2 due to widespread conversions into aquaculture. The paper unravels the complex dynamics between land-cover change, socio-economic development and associated land-use policies, which have significant implications for the change in rural landscapes.